Becoming Hitler : the making of a Nazi - Weber, Thomas, 1974- (Oxford, United Kingdom : Oxford University Press, 2017)
"An award-winning historian charts Hitler's radical transformation after World War I from a directionless loner into a powerful National Socialist leader. In Becoming Hitler, award-winning historian Thomas Weber examines Adolf Hitler's time in Munich between 1918 and 1926, the years when Hitler shed his awkward, feckless persona and transformed himself into a savvy opportunistic political operator who saw himself as Germany's messiah. The story of Hitler's transformation is one of a fateful match between man and city. After opportunistically fluctuating between the ideas of the left and the right, Hitler emerged as an astonishingly flexible leader of Munich's right-wing movement. The tragedy for Germany and the world was that Hitler found himself in Munich; had he not been in Bavaria in the wake of the war and the revolution, his transformation into a National Socialist may never have occurred. In Becoming Hitler, Weber brilliantly charts this tragic metamorphosis, dramatically expanding our knowledge of how Hitler became a lethal demagogue"--
Prelude -- PART I: Genesis -- Coup d'état (20 November 1918-February 1919) -- A Cog in the Machine of Socialism (February-early April 1919) -- Arrested (early April-early May 1919) -- Turncoat (early May to mid-July 1919) -- PART II: New Testaments -- A New Home at Last (mid-July to September 1919) -- Two Visions (October 1919-March 1920) -- A Two and a Half Thousand Year Old Tool (March-August 1920) -- Genius (August-December 1920) -- Hitler's Pivot to the East (December 1920-July 1921) -- PART III: Messiah -- The Bavarian Mussolini (July 1921-December 1922) -- The German Girl from New York (early 1923-summer 1923) -- Hitler's First Book (summer 1923-autumn 1923) -- The Ludendorff Putsch (autumn 1923-spring 1924) -- Lebensraum (spring 1924-1926) -- Epilogue -- Archival collections & private papers and interviews.
Includes bibliographical references (pages 393-407) and index.
Keywords: Hitler, Adolf, -- 1889-1945.; Hitler, Adolf, -- 1889-1945 -- Homes and haunts -- Germany -- Munich; Hitler, Adolf, -- 1889-1945 -- Psychology; Nazis -- Germany -- Biography; Right-wing extremists -- Germany -- Biography; Heads of state -- Germany -- Biography; National socialism -- History; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; BIOGRAPHY & AUTOBIOGRAPHY / Historical; BIOGRAPHY & AUTOBIOGRAPHY / Political; HISTORY / Europe / Germany; Germany -- Politics and government -- 1918-1933.